1978
DOI: 10.1084/jem.147.4.1106
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory circuits among T-cell sets. I. T-helper cells induce other T-cell sets to exert feedback inhibition.

Abstract: The T-lymphocyte population is divisible into several subclasses; each subclass possesses a distinctive genetic program which combines information for cell-surface phenotype and function (1). In the mouse, there is evidence that T cells which express the Thyl+Lyl+Ly23 -surface phenotype CLyl cells") are programmed for helper (TH) 1 function. In contrast, T cells that express the Thyl+Lyl-Ly23 ÷ surface phenotype CLy23 cells") are programmed for suppressor (Ts) function (1). Isolation of these two T-cell subcla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
107
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(115 citation statements)
references
References 14 publications
8
107
0
Order By: Relevance
“…In fact, there is very little information demonstrating how T regulatory cells become activated in vivo. Nevertheless, an important parallel between CD4 and CD8 suppressor cells is the fact that elimination of either population renders mice more susceptible to autoimmunity, which is reminiscent of classical studies showing collaboration between CD4 and CD8 suppressor cells (41,42). Another similarity between CD4 and CD8 suppressor cells is the evidence of TGF-␤-independent mechanisms of suppression.…”
Section: Discussionmentioning
confidence: 84%
“…In fact, there is very little information demonstrating how T regulatory cells become activated in vivo. Nevertheless, an important parallel between CD4 and CD8 suppressor cells is the fact that elimination of either population renders mice more susceptible to autoimmunity, which is reminiscent of classical studies showing collaboration between CD4 and CD8 suppressor cells (41,42). Another similarity between CD4 and CD8 suppressor cells is the evidence of TGF-␤-independent mechanisms of suppression.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, this type of T-T interaction plays a physiological role in the regulation of the in vivo immune response in man. More recently, Eardley et al (14) and Cantor and co-workers (15,16) showed that in mice, the maintenance of immunological homeostasis was governed by the Qal feedback inhibitory circuit. These studies indicate that Lyl Qal+ cells induce Lyl, 2, 3, Qal+ cells to generate potent feedback inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies demonstrate that removal of JRA+ cells with antibody and complement results in a three-to sixfold enhancement of immunoglobulin production in a pokeweed mitogen-driven system. Both the cellular expression ofantigen(s) defined by JRA autoantibody and augmentation of immunoglobulin synthesis suggests that JRA antisera might define the equivalent of a Qal-like antigen found on the inducer population for the suppression and/or feedback regulatory subset in man (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…The augmented primary immune response observed in the present study could have resulted from a defect in antigen nonspecific suppression, such as a defect in Ly-1+2+3 + feedback suppression (5,6). Perhaps the relatively normal secondary NZB CTL responses observed herein, reflect normal antigen-specific regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 63%